Pendapatan dan Strategi Pemasaran pada Usaha Budidaya Ikan Cupang (Betta Splendens) di Kabupaten Mojokerto - Pratama, Mohammad Aditya Budi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
Betta fish experienced a drastic decline in trend/popularity, previously experiencing a peak in popularity from October 2020 to early February 2021. The decline in trend of betta fish also affected the income and sustainability of betta fish cultivation in Mojokerto. The purpose of this research is to determine the difference in income from betta fish cultivation businesses in Mojokerto when the trend for betta fish is rising and decreasing, and to find out effective marketing strategies that can be applied to betta fish cultivation businesses in Mojokerto. This research uses analytical and comparative research methods, and this research analyzes primary data obtained from interviews with 12 respondents who are Betta fish cultivators in Mojokerto. The data was then analyzed using SWOT analysis, and income analysis. The research results show that the average income per month when betta fish trend increases is IDR. 80,658,121/month, to Rp. 7,417,288/month when trend for betta fish is decreasing. Then the strategy that can be implemented is to support aggressive strategic policies through the S-O (Strengths-Opportunities) strategy. These strategies include: cultivating and selling various types of quality betta fishs, strengthening and expanding local and export markets, and providing delivery guarantees for customers from outside region.